Corneal biomechanical metrics of healthy Chinese adults using Corvis ST. Issue 2 (April 2017) - Wang, Wei; He, Miao; He, Hong; Zhang, Chi; Jin, He; Zhong, Xingwu
Abstract: Purpose: To evaluate the corneal biomechanical metrics by Corvis ST (CST) in healthy Chinese adults. Methods: This cross-sectional study used CST to measure intraocular pressure (IOP), central corneal thickness (CCT), and corneal biomechanical parameters, including time, velocity, length, deformation amplitude at the first (A1T, A1V, A1L, A1DA) and second applanation (A2T, A2V, A2L, A2DA), time, radius curvature and deformation amplitude at highest concavity (HCT, HCR, HCDA) and peak distance (PD). Results: A total of 158 healthy adults (158 eyes) were included in the final analysis. No significant differences were observed between male and female for any biomechanical parameters (All P > 0.05). With increasing age, a significant trend of increase was detected among A1V, A1DA, A2T, A2DA, and HCDA (All P < 0.05). The A1T decreased significantly with increasing age (P < 0.001). The cluster analysis using Pearson coefficient divided the CST parameters into 5 sub-clusters, where IOP, A1T, A2V had strongest relation. The multivariable linear regression analyses demonstrated that age was independently associated with A1DA, A2DA, and HCDA. The IOP was positively associated with A1T, A2V, and HCR, while negatively with A1V, A2T, HCT, PD, and HCDA. The CCT was positively correlated with A1L, A1DA, A2L, A2V, or HCR. Conclusions: CST provided informative corneal biomechanical measurements in this Chinese population. Most corneal biomechanical parameters were associated with IOP, and several parameters were influenced by age or CCT, suggesting adjustment of these factors was needed before interpretations of CST outputs.